2021
DOI: 10.3390/ijms22042127
|View full text |Cite
|
Sign up to set email alerts
|

Fructose Induces Fluconazole Resistance in Candida albicans through Activation of Mdr1 and Cdr1 Transporters

Abstract: Candida albicans is a pathogenic fungus that is increasingly developing multidrug resistance (MDR), including resistance to azole drugs such as fluconazole (FLC). This is partially a result of the increased synthesis of membrane efflux transporters Cdr1p, Cdr2p, and Mdr1p. Although all these proteins can export FLC, only Cdr1p is expressed constitutively. In this study, the effect of elevated fructose, as a carbon source, on the MDR was evaluated. It was shown that fructose, elevated in the serum of diabetics,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 52 publications
2
18
0
Order By: Relevance
“…Candidiasis treatment is no exception in this case, and it is important to take into consideration the effects of compounds that naturally occur in niches where C. albicans is present in the body. Recently, our research showed that fructose activates Mdr1 and Cdr1 transporters in C. albicans in response to the presence of FLC [ 18 ]. Furthermore, we demonstrated that capric acid produced by probiotic yeast Saccharomyces boulardii influences the susceptibility of C. albicans to FLC and AmB [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Candidiasis treatment is no exception in this case, and it is important to take into consideration the effects of compounds that naturally occur in niches where C. albicans is present in the body. Recently, our research showed that fructose activates Mdr1 and Cdr1 transporters in C. albicans in response to the presence of FLC [ 18 ]. Furthermore, we demonstrated that capric acid produced by probiotic yeast Saccharomyces boulardii influences the susceptibility of C. albicans to FLC and AmB [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Electrophoretic separation and transfer of Cdr1p- GFP was also performed as previously described [ 42 ]. For detection, a monoclonal mouse anti- GFP primary antibody was used, followed by an HRP-conjugated rabbit anti-mouse secondary antibody [ 18 ]. The remaining steps were performed as described [ 42 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prophylaxis with antifungal agents leads to the emergence of resistant strains [12,20], especially to azole antifungals [21].…”
Section: Introductionmentioning
confidence: 99%